Perspective on enhancing quality of life in oral cancer patients: Integrative approaches and comprehensive care - Sohaib Arshad; Shazia Fathima Jaffer Hussain; Selvaraj Jayaram; Vishnu Priya Veeraraghavan; Mohmed Isaqali Karobari (Oral Oncology Reports)
Oral cancer poses a global health challenge with high morbidity and mortality rates. Treatments, including surgery, radiation, and chemotherapy, profoundly impact patients' quality of life (QoL). Enhancing QoL requires a comprehensive approach that integrates physical health management, psychological support, social support, and integrative and palliative care.Effective pain management, nutritional support, and oral rehabilitation are crucial for maintaining physical health. Psychological support through counseling, psychotherapy, and mind-body interventions addresses emotional distress. Social support from family, caregivers, and community resources is essential for practical and emotional needs. Integrative care approaches and early palliative care provide holistic, patient-centered solutions.This manuscript emphasizes the necessity of a holistic approach to improve the QoL for oral cancer patients, advocating for comprehensive, compassionate care plans that address physical, emotional, and social dimensions.